KAJIAN KINERJA SISTEM POLDER DENGAN BALANCE SCORECARD - Mega Asiska Ninda Pratiwi; Nuraini Nuraini; Hari Nugroho; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2016)
Semarang especially in coastal area or better known as “Semarang bawah” has experienced land subsidence by 7 cm / year. This makes the ground water level in that area is lower than sea level. The result was a tidal flood happened in Semarang. The government tried to solve this problem by making Polder system. However, the fact is in the rainy season in the coastal areas was still flooding in. In other words, the performance of polder system was not optimal. Some polders that were used to assess the performance of polder in this study have not been able to reduce the impact of flood optimally. Therefore, it needed studies performance of each polder to determine polder ability in overcoming the flood. This study observed 4 polders in Semarang, which are Semarang River Polder, Banger Polder, Tanah Mas Polder and Tawang Polder. This performance is measured by the five critical areas that became reference of Balance Scorecard in assessment, that are Agency Management, Customer Satisfaction, Internal Processes, Finance and Expenditure & Development. The method used is descriptive analysis, quantitative and weighting with AHP (Analytical Hierarchy Process). Balance Scorecard method on a field tested performance different weights on each field performance. The result of different weighting, which is calculated using the AHP is obtained ranks as follows Tanah Mas Polder (370/500), Banger Polder (348/500), Tawang Polder (296/500) dan Semarang River Polder (287/500). The result calculation of polder effectiveness is the polder ability in reducing flood at Polder Banger by 56% and Semarang River Polder by 59%.